The The ethical decision-making of the journalists in the UAE - Zayed, Asma Rashed (Al-Adab Journal, 2022)
Journalists have a great responsibility in relation to the news published and presented to the public as they collect, analyze, and write news stories. Many questions revolve around the journalists' practices concerning the duties that they must commit to in their profession. This study aims to explore the state of ethical decision-making among journalists in the UAE and the extent to which education as a factor influences their practices. The study results show that most journalists were unable to make an ethical and fair decision in the ethical dilemmas that they may face while performing their job. Education has also been shown to have a definite influence on ethical decision-making.